The Impact of Shariah Law, Liquidity and Interest Rate on Sukuk Growth in Malaysia in Short and Long run: The ARDL Estimation - Al-Fakih, Dheya Hamood Saif; Zakaria, Shahsuzan; Ismail, Md Khairu Amin (The Indonesian Capital Market Review, 2026)
The issuance of sukuk has been steadily increasing over time, underscoring its growing significance and the need for further scholarly examination. As a global leader in the Islamic finance industry and a prominent issuer of sukuk, Malaysia serves as a critical case study for understanding this phenomenon. It is essential to investigate various factors and their impact on the growth of sukuk. The study analyzes the relationship between sukuk growth and factors such as interest rate, liquidity (M1), and Shariah law using monthly data from April 2011 to December 2020 obtained from Thomson Reuters Eikon. The study employs the ARDL model and the Cointegration test, revealing a long-term cointegration relationship among the variables. In the long term, sukuk growth is positively influenced by liquidity (M1) and Shariah law but not by interest rate, while in the short term, all variables show a significant effect.